Chrześcijańska interpretacja kilku antycznych gemm - Ryś, Anna (Vox Patrum, 2016)
The article presents the Christian interpretation of four ancient gems from the collection of Cabinet des médailles (department of French National Library). Next to the role of the objects in medieval tradition the history of the gems is presented. An attempt at explaining the reasons of using the gems in Christian cult is made.